Controlling microstructure and film growth of relaxor-ferroelectric thin films for high break-down strength and energy-storage performance. Issue 1 (January 2018) - Nguyen, Minh D.; Nguyen, Chi T.Q.; Vu, Hung N.; Rijnders, Guus
Abstract: The relaxor ferroelectric Pb0.9 La0.1 (Zr0.52 Ti0.48 )O3 (PLZT) thin films were deposited using pulsed laser deposition, and their microstructures, break-down field strengths and energy storage performances were investigated as a function of the buffer layer and electrode. A large recoverable energy-storage density ( U reco ) of 23.2 J/cm 3 and high energy-storage efficiency ( η ) of 91.6% obtained in the epitaxial PLZT film grown on SrRuO3 /SrTiO3 /Si are much higher than those in the textured PLZT film ( U reco = 21.9 J/cm 3, η = 87.8%) on SrRuO3 /Ca2 Nb3 O10 -nanosheet/Si and the polycrystalline PLZT film ( U reco = 17.6 J/cm 3, η = 82.6%) on Pt/Ti/SiO2 /Si, under the same condition of 1500 kV/cm and 1 kHz, due to the slim polarization loop and significant antiferroelectric-like behavior. Owing to the high break-down strength (BDS) of 2500 kV/cm, a giant U reco value of 40.2 J/cm 3 was obtained for the epitaxial PLZT film, in which U reco values of 28.4 J/cm 3 (at BDS of 2000 kV/cm) and 20.2 J/cm 3 (at BDS of 1700 kV/cm), respectively, were obtained in the textured and polycrystalline PLZT films. The excellent fatigue-free properties and high thermal stability were also observed in these films.